백서의 패혈증 모델에서 시간에 따른 폐조직에서의 Inducible Nitric Oxide Synthase 발현 - 김중희; 권운용; 서길준; 윤여규; 김성춘 (Daehan oe'sang haghoeji, 2008)
Purpose: Many studies on the time course of inducible nitric oxide synthase (iNOS) gene expression have been performed in the LPS (Lipopolysaccharide)-induced endotoxemic model, but there have been few experimental approaches to continuous peritonitis-induced sepsis model. We conducted this study to establish basic data for future sepsis-related research by investigating the time course of iNOS gene expression and the relationship with the production of inflammatory mediators in the early sepsis model induced by cecal ligation and puncture (CLP). Methods: Male Sprague-Dawley rats were operated on by sing the CLP method to induce of peritonitis; and then, they were sacrificed and samples of blood and lung tissues were obtained at various times (1,2,3,6,9 and 12 h after CLP). We observed the expression of iNOS mRNA from lung tissues and measured the synthesis of nitric oxide, IL-1β, and TNF-αfrom the blood. Results: iNOS mRNA began to be expressed at 3 h and was maintained untill 12 h after CLP. The nitric oxide concentration was increased significantly at 6 h, reached its peak level at 9 h, and maintained a plateau untill 12 h after CLP. TNF-αbegan to be detected at 3 h, increased gradually, and decreased steeply from 9 h after CLP. IL-1βshowed its peak level at 6 h after CLP, and tended to decrease without significance. Conclusion: We observed that the iNOS gene was expressed later in peritonitis-induced sepsis than in LPSinduced sepsis. Nitric oxide and key inflammatory mediators were also expressed later in peritonitis-induced sepsis than in LPS-induced sepsis. (J Korean Soc Traumatol 2008;21:120-127) KCI Citation Count: 0